2020
DOI: 10.1002/dneu.22744
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cell interactions during the development of the peripheral nervous system

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 249 publications
(348 reference statements)
0
51
0
Order By: Relevance
“…In the direct coculture experiment, both cbMSCs and SCLCs exhibited a further increased potential in promoting neurite sprouting, especially the SCLC group. As the native SCs have close and complex interactions with axons (Wilson et al, 2020), it is not surprise that the direct interaction between SCLCs and SH-SY5Y cells could achieved the best result in stimulating neurite formation and elongation. Collectively, our results clearly demonstrated that cbMSCs can be phenotypically, epigenetically, FIGURE 3 | SCLCs were assembled into three-dimensional (3D) spheroids to enhance their therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…In the direct coculture experiment, both cbMSCs and SCLCs exhibited a further increased potential in promoting neurite sprouting, especially the SCLC group. As the native SCs have close and complex interactions with axons (Wilson et al, 2020), it is not surprise that the direct interaction between SCLCs and SH-SY5Y cells could achieved the best result in stimulating neurite formation and elongation. Collectively, our results clearly demonstrated that cbMSCs can be phenotypically, epigenetically, FIGURE 3 | SCLCs were assembled into three-dimensional (3D) spheroids to enhance their therapeutic potential.…”
Section: Discussionmentioning
confidence: 99%
“…In the healthy PNS, Schwann cells myelinate peripheral nerves, increasing the conduction velocity of axonal impulses [ 36 ] (depicted in Figure 2 A). However, the abundant population of Schwann cells in the PNS serves many purposes outside of their role as the neuron-myelinating cell [ 37 ]. This includes enhancing and guiding axon regeneration, calcium signaling to modulate synaptic neurotransmission, and chemokine signaling to recruit nearby cells [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospun fiber scaffolds are used to create in vitro culture systems that recapitulate the topographical features of axons in peripheral nerves and white matter tracts in the spinal cord, allowing for increased physiological relevance when studying interactions between glia and neurons in culture [ 37 , 45 , 48 ]. Additionally, electrospun fibers are readily incorporated into synthetic nerve grafts and assessed using in vivo animal models for their ability to support the infiltration of glia and axonal regeneration across the length of the injury [ 15 , 16 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…121,122 Detailed reviews of Schwann cell development can be found elsewhere. [123][124][125][126] Recent work from several laboratories has highlighted how inhibition of the Hippo pathway, with consequent activation of YAP/TAZ, is essential for multiple steps of normal Schwann cell development, including radial sorting, proliferation and subsequent myelination. 92,127,128 YAP/TAZ are expressed throughout the Schwann cell lineage, but TAZ expression is higher between P3 and P15, the period corresponding to active radial sorting and myelination.…”
Section: Dorsal Root Ganglia Neurons and Satellite Cellsmentioning
confidence: 99%